Effects of pre-trial response requirements on self-control choices by rats and pigeons. - Mazur, James E (Journal of the experimental analysis of behavior, 2012)
Parallel experiments with rats and pigeons examined whether the size of a pre-trial ratio requirement would affect choices in a self-control situation. In different conditions, either 1 response or 40 responses were required before each trial. In the first half of each experiment, an adjusting-ratio schedule was used, in which subjects could choose a fixed-ratio schedule leading to a small reinforcer, or an adjusting-ratio schedule leading to a larger reinforcer. The size of the adjusting ratio requirement was increased and decreased over trials based on the subject's responses, in order to estimate an indifference point-a ratio at which the two alternatives were chosen about equally often. The second half of each experiment used an adjusting-delay procedure-fixed and adjusting delays to the small and large reinforcers were used instead of ratio requirements. In some conditions, particularly with the reinforcer delays, the rats had consistently longer adjusting delays with the larger pre-trial ratios, reflecting a greater tendency to choose the larger, delayed reinforcer when more responding was required to reach the choice point. No consistent effects of the pre-trial ratio were found for the pigeons in any of the conditions. These results may indicate that rats are more sensitive to the long-term reinforcement rates of the two alternatives, or they may result from a shallower temporal discounting rate for rats than for pigeons, a difference that has been observed in previous studies.
10 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Psychology Department, Southern Connecticut State University, New Haven, CT 06515, USA. mazurj1@southernct.edu
Keywords: *Choice Behavior; *Conditioning; Operant; *Reinforcement Schedule; Animals; Choice Behavior; Columbidae; Conditioning; Operant; Long Evans rat; Male; Rats; Rats; Long-Evans; Reinforcement Schedule; animal; article; decision making; dept.psy; instrumental conditioning; male; peer-reviewed; pigeons and doves; rat; reinforcement

Distributed versus exclusive preference in discrete-trial choice. - Mazur, James E (Journal of Experimental Psychology: Animal Behavior Processes, 2010)
Two experiments on discrete-trial choice examined the conditions under which pigeons would exhibit exclusive preference for the better of two alternatives as opposed to distributed preference (making some choices for each alternative). In Experiment 1, pigeons chose between red and green response keys that delivered food after delays of different durations, and in Experiment 2 they chose between red and green keys that delivered food with different probabilities. Some conditions of Experiment 1 had fixed delays to food and other conditions had variable delays. In both experiments, exclusive or nearly exclusive preference for the better alternative was found in some conditions, but distributed preference was found in other conditions, especially in Experiment 2 when key location varied randomly over trials. The results were used to evaluate several different theories about discrete-trial choice. The results suggest that exclusive preference for one alternative is a frequent outcome in discrete-trial choice. When distributed preference does occur, it is not the result of inherent tendencies to sample alternatives or to match response percentages to the values of the alternatives. Rather, distributed preference may occur when two factors (such as reinforcer delay and position bias) compete for the control of choice, or when the consequences for the two alternatives are similar and difficult to discriminate.
9 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Psychology Department, Southern Connecticut State University, New Haven, CT 06515, USA. mazurj1@southernct.edu
Keywords: *Choice Behavior/ph [Physiology]; *Conditioning; Operant/ph [Physiology]; *Reinforcement Schedule; *Reinforcement; Psychology; Animals; Choice Behavior; Columba; Columbidae; Conditioning; Operant; Discrete-trial choice; Exclusive preference; Male; Pigeons; Probability; Reaction Time; Reaction Time/ph [Physiology]; Reinforcement (Psychology); Reinforcement Schedule; Reinforcer delay; Time Factors; animal; article; decision making; dept.psy; instrumental conditioning; male; physiology; pigeons and doves; probability; reaction time; reinforcement; time

Rats' choices with token stimuli in concurrent variable- interval schedules - Mazur, James E. (Journal of the Experimental Analysis of Behavior, 2014)
Four rats responded on concurrent variable-interval schedules that delivered token stimuli (stimulus lights arranged vertically above each of two side levers). During exchange periods, each token could be exchanged for one food pellet by responding on a center lever, with one response required for each pellet delivery. In different conditions, the exchange requirements (number of tokens that had to be earned before they could be exchanged for food) varied between one and four for the two response levers. The experiments were closely patterned after research with pigeons by Mazur and Biondi (), and the results from the rats in the present experiment were similar. Response percentages on the two levers changed as each additional token was earned, and these patterns indicated that choice was controlled by both the time to the exchange periods and the number of food pellets that were delivered in the exchange period. In some conditions, the exchange requirement was three tokens for each lever, but the token lights were not turned on as they were earned for one of the two keys. The rats showed a slight preference for the lever without the token lights, which may indicate that the token lights were not serving as conditioned reinforcers (a result also found by Mazur and Biondi with pigeons). Overall, these results suggest that, in this choice procedure, the token stimuli served primarily as discriminative stimuli that signaled the temporal proximity and quantity of the primary reinforcer, food.
0 citations (Crossref) [2023-10-31] tex.eissn: 1938-3711 tex.researcherid-numbers: Mazur, James/AAA-6971-2019 tex.unique-id: ISI:000341714000004
Keywords: Animals; Choice Behavior; Concurrent variable-interval schedules; Conditioned reinforcers; Conditioning; Operant; Cues; Discriminative stimuli; Hyperbolic discounting; Lever press; Long Evans rat; Male; Rats; Rats; Long-Evans; Reinforcement Schedule; Token Economy; Token stimuli; animal; association; decision making; dept.psy; instrumental conditioning; male; peer-reviewed; rat; reinforcement

Mathematical models and the experimental analysis of behaviour - Mazur, James E (Journal of the Experimental Analysis of Behavior, 2006)
The rise of mathematical models in the experimental analysis of behavior has increased over the years, and they offer several advantages. Mathematical models require theorists to be precise and unambiguous, often allowing comparisons of competing theories that sound similar when stated in words. Sometimes different mathematical models may make equally accurate predictions for a large body of data. In Such cases, it is important to find and investigate situations for which the competing models make different predictions because, unless two models are actually mathematically equivalent, they are based on different assumptions about the psychological processes that underlie ail observed behavior. Mathematical models developed in basic behavioral research have been used to predict and control behavior in applied settings, and they have guided research in other areas of psychology. A good mathematical model call provide a common framework for understanding what might otherwise appear to be diverse and unrelated behavioral phenomena. Because psychologists vary in their quantitative skills and in their tolerance for mathematical equations, it is important for those who develop mathematical models of behavior to find ways (such as verbal analogies, pictorial representations, or concrete examples) to communicate the key premises of their models to nonspecialists.
81 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/006-251-406-775-565 tex.type: [object Object]
Keywords: *Models; Theoretical; *Social Behavior; Behavior; Equations; Humans; Mathematical models; Models; Theoretical; Reinforcement; Reinforcement (Psychology); Reinforcement; Psychology; Social Behavior; article; dept.psy; human; peer-reviewed; reinforcement; social behavior; theoretical model

Rats’ choices between one and two delayed reinforcers - Mazur, James E (Learning & Behavior, 2007)
Rats chose between alternatives that differed in the number of reinforcers and in the delay to each reinforcer. A left leverpress led to two reinforcers, each delivered after a fixed delay. A right leverpress led to one reinforcer after an adjusting delay. The adjusting delay was increased or decreased many times in a session, depending on the rat's choices, in order to estimate an indifference point-a delay at which the two alternatives were chosen about equally often. Both the number of reinforcers and their individual delays affected the indifference points. The overall pattern of results was well described by the hyperbolic-decay model, which states that each additional reinforcer delivered by an alternative increases preference for that alternative but that a reinforcer's effect is inversely related to its delay. Two other possible delay-discounting equations, an exponential equation and a reciprocal equation, did not produce satisfactory predictions for these data. Adding an additional free parameter to the hyperbolic equation as an exponent for delay did not appreciably improve the predictions, suggesting that raising delay to some power other than 1.0 was unnecessary. The results were qualitatively similar to those from a previous experiment with pigeons (Mazur, 1986), but quantitative differences suggested that the rates of delay discounting were several times slower for rats than for pigeons.
24 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/057-943-120-320-01X tex.type: [object Object]
Keywords: *Choice Behavior; *Conditioning; Operant; *Motivation; *Reinforcement Schedule; *Time Perception; Animals; Male; Models; Theoretical; Rats; Rats; Sprague-Dawley; animal behavior; animal experiment; article; conditioning; dept.psy; hyperbolic decay model; mathematical model; nonhuman; pigeon; predictive validity; rat; reinforcement

Effects of reinforcer delay and variability in a successive-encounters procedure. - Mazur, James E (Learning & behavior, 2008)
Pigeons responded in a successive-encounters procedure that consisted of a search period, a choice period, and a handling period. The search period was either a fixed-interval or a mixed-interval schedule presented on the center key of a three-key chamber. Upon completion of the search period, the center key was turned off and the two side keys were lit. A pigeon could either accept a delay followed by food (by pecking the right key) or reject this option and return to the search period (by pecking the left key). During the choice period, a red right key represented the long alternative (a long handling delay followed by food), and a green right key represented the short alternative (a short handling delay followed by food). The experiment consisted of a series of comparisons for which optimal diet theory predicted no changes in preference for the long alternative (because the overall rates of reinforcement were unchanged), whereas the hyperbolic-decay model predicted changes in preference (because the delays to the next possible reinforcer were varied). In all comparisons, the results supported the predictions of the hyperbolic-decay model, which states that the value of a reinforcer is inversely related to the delay between a choice response and reinforcer delivery.
1 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Psychology Department, Southern Connecticut State University, New Haven, CT 06515, USA. mazurj1@southernct.edu
Keywords: *Choice Behavior; *Reinforcement; Psychology; Animals; Behavior; Animal; Choice Behavior; Columbidae; Male; Reinforcement (Psychology); Time Factors; animal; animal behavior; animal experiment; article; conditioning; controlled study; decision making; dept.psy; food; male; nonhuman; pigeon; pigeons and doves; psychological theory; reinforcement; time

Choice between single and multiple reinforcers in concurrent-chains schedules. - Mazur, James E (Journal of the experimental analysis of behavior, 2006)
Pigeons responded on concurrent-chains schedules with equal variable-interval schedules as initial links. One terminal link delivered a single reinforcer after a fixed delay, and the other terminal link delivered either three or five reinforcers, each preceded by a fixed delay. Some conditions included a postreinforcer delay after the single reinforcer to equate the total durations of the two terminal links, but other conditions did not include such a postreinforcer delay. With short initial links, preference for the single-reinforcer alternative decreased when a postreinforcer delay was present, but with long initial links, the postreinforcer delays had no significant effect on preference. In conditions with a postreinforcer delay, preference for the single-reinforcer alternative frequently switched from above 50% to below 50% as the initial links were lengthened. This pattern of results was consistent with delay-reduction theory (Squires & Fantino, 1971), but not with the contextual-choice model (Grace, 1994) or the hyperbolic value-added model (Mazur, 2001) as they have usually been applied. However, the hyperbolic value-added model could account for the results if its calculations were expanded to include reinforcers delivered in later terminal links. The implications of these findings for models of concurrent-chains performance are discussed.
4 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Psychology Department, Southern Connecticut State University, New Haven 06515, USA. mazurj1@southernct.edu
Keywords: *Appetitive Behavior; *Choice Behavior; *Motivation; *Reinforcement Schedule; Animals; Appetitive Behavior; Association Learning; Choice Behavior; Columbidae; Concurrent chains; Contextual-choice model; Delay-reduction theory; Discrimination Learning; Hyperbolic value-added model; Key peck; Motivation; Multiple reinforcers; Pigeons; Psychomotor Performance; Reinforcement Schedule; animal; appetite; article; decision making; dept.psy; discrimination learning; learning; motivation; peer-reviewed; pigeons and doves; psychomotor performance; reinforcement

Choice in a successive-encounters procedure and hyperbolic decay of reinforcement. - Mazur, James E (Journal of the experimental analysis of behavior, 2007)
Pigeons responded in a successive-encounters procedure that consisted of a search state, a choice state, and a handling state. The search state was either a fixed-interval or mixed-interval schedule presented on the center key of a three-key chamber. Upon completion of the search state, the choice state was presented, in which the center key was off and the two side keys were lit. A pigeon could either accept a delay followed by food (by pecking the right key) or reject this option and return to the search state (by pecking the left key). During the choice state, a red right key represented the long alternative (a long handling delay followed by food), and a green right key represented the short alternative (a short handling delay followed by food). In some conditions, both the short and long alternatives were fixed-time schedules, and in other conditions both were mixed-time schedules. Contrary to the predictions of both optimal foraging theory and delay-reduction theory, the percentage of trials on which pigeons accepted the long alternative depended on whether the search and handling schedules were fixed or mixed. They were more likely to accept the long alternative when the search states were fixed-interval rather than mixed-interval schedules, and more likely to reject the long alternative when the handling states were fixed-time rather than mixed-time schedules. This pattern of results was in qualitative agreement with the predictions of the hyperbolic-decay model, which states that the value of a reinforcer is inversely related to the delay between a choice response and reinforcer delivery.
6 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Southern Connecticut State University, Psychology Department, New Haven 06515, USA. mazurj1@southernct.edu
Keywords: *Choice Behavior; *Reinforcement; Psychology; Animals; Choice; Choice Behavior; Columbidae; Delay-reduction theory; Hyperbolic-decay model; Key peck; Male; Optimal foraging theory; Pigeons; Reinforcement (Psychology); Successive-encounters procedure; animal; article; decision making; dept.psy; male; peer-reviewed; pigeons and doves; reinforcement

Species differences between rats and pigeons in choices with probabilistic and delayed reinforcers - Mazur, James E. (Behavioural Processes, 2007)
An adjusting-delay procedure was used to study rats' choices with probabilistic and delayed reinforcers, and to compare them with previous results from pigeons. A left lever press led to a 5-s delay signaled by a light and a tone, followed by a food pellet on 50% of the trials. A right lever press led to an adjusting delay signaled by a light followed by a food pellet on 100% of the trials. In some conditions, the light and tone for the probabilistic reinforcer were present only on trials that delivered food. In other conditions, the light and tone were present on all trials that the left lever was chosen. Similar studies with pigeons [Mazur, J.E., 1989. Theories of probabilistic reinforcement. J. Exp. Anal. Behav. 51, 87-99; Mazur, J.E., 1991. Conditioned reinforcement and choice with delayed and uncertain primary reinforcers. J. Exp. Anal. Behav. 63, 139-150] found that choice of the probabilistic reinforcer increased dramatically when the delay-interval stimuli were omitted on no-food trials, but this study found no such effect with the rats. In other conditions, the probability of food was varied, and comparisons to previous studies with pigeons indicated that rats showed greater sensitivity to decreasing reinforcer probabilities. The results support the hypothesis that rats' choices in these situations depend on the total time between a choice response and a reinforcer, whereas pigeons' choices are strongly influenced by the presence of delay-interval stimuli. (c) 2007 Elsevier B.V. All rights reserved.
23 citations (Crossref) [2023-10-31] Meeting of the Society-for-the-Quantitative-Analyses-of-Behavior (SQAB 2006), Atlanta, GA, MAY 26-27, 2006 Citation Key Alias: lens.org/092-975-244-015-987 tex.organization: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: *Association Learning/ph [Physiology]; *Choice Behavior/ph [Physiology]; *Probability Learning; *Reinforcement; Psychology; *Time Perception/ph [Physiology]; Animals; Columba; Columbidae; Delay-interval stimuli; Delayed reinforcers; Probabilistic reinforcers; Rats; Rats; Sprague-Dawley; Rattus; Species Specificity; Time Factors; animal experiment; article; behavioral response; controlled study; decision making; dept.psy; food; food intake; gamebird; nonhuman; probability; rat; reinforcement; rodent; species difference; stimulus

Learning and behavior, 5th ed. - Mazur, James E. (2002)
Keywords: dept.psy

Effects of reinforcer probability, delay, and response requirements on the choices of rats and pigeons: Possible species differences - Mazur, James E (Journal of the Experimental Analysis of Behavior, 2005)
In Experiment 1 with rats, a left lever press led to a 5-s delay and then a possible reinforcer. A right lever press led to an adjusting delay and then a certain reinforcer. This delay was adjusted over trials to estimate an indifference point, or a delay at which the two alternatives were chosen about equally often. Indifference points increased as the probability of reinforcement for the left lever decreased. In some conditions with a 20% chance of food, a light above the left lever was lit during the 5-s delay on all trials, but in other conditions, the light was only lit on those trials that ended with food. Unlike previous results with pigeons, the presence or absence of the delay light on no-food trials had no effect on the rats' indifference points. In other conditions, the rats showed less preference for the 20% alternative when the time between trials was longer. In Experiment 2 with rats, fixed-interval schedules were used instead of simple delays, and the presence or absence of the fixed-interval requirement on no-food trials had no effect on the indifference points. In Experiment 3 with rats and Experiment 4 with pigeons, the animals chose between a fixed-ratio 8 schedule that led to food on 33% of the trials and an adjusting-ratio schedule with food on 100% of the trials. Surprisingly, the rats showed less preference for the 33% alternative in conditions in which the ratio requirement was omitted on no-food trials. For the pigeons, the presence or absence of the ratio requirement on no-food trials had little effect. The results suggest that there may be differences between rats and pigeons in how they respond in choice situations involving delayed and probabilistic reinforcers.
19 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/053-049-743-382-047 tex.type: [object Object]
Keywords: *Behavior; Animal/ph [Physiology]; *Choice Behavior; *Reaction Time; *Reinforcement; Psychology; Animals; Behavior; Animal; Choice; Choice Behavior; Columbidae; Delay; Fixed interval; Fixed ratio; Key peck; Lever press; Male; Pigeons; Probability; Rats; Rats; Sprague-Dawley; Reaction Time; Reinforcement (Psychology); Species Specificity; Sprague Dawley rat; animal; animal behavior; decision making; dept.psy; male; peer-reviewed; physiology; pigeons and doves; probability; rat; reaction time; reinforcement; review; species difference

Tradeoffs among delay, rate, and amount of reinforcement - Mazur, James E (Behavioural Processes, 2000)
In Experiment I, an adjusting-delay procedure was used to measure pigeons' choices between a single delayed reinforcer and a range of different variable-time schedules. Indifference points showed an inverse relation between rate of reinforcement and delay that was well described by a hyperbolic equation. An adjusting-amount procedure was used in Experiment 2, in which pigeons chose between an adjusting amount of food delivered after a 0.5-s delay and 3 s of food delivered after a range of different delays, and the effects of delay were similar to those found in Experiment 1. The results from both experiments indicated that, for pigeons, the strength of a reinforcer decreased rapidly with increasing delay. Estimates of a decay rate parameter in the hyperbolic equation were similar to those found in other studies with pigeons, but the rates of temporal discounting were three or four times faster than those found in studies with rats, suggesting a possible species difference. (C) 2000 Published by Elsevier Science B.V. All rights reserved.
64 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/026-033-972-981-013 tex.type: [object Object]
Keywords: Adjusting procedure; Amount of reinforcement; Delay; Discounting; Key peck; Pigeons; Rate of reinforcement; animal experiment; article; behavior; controlled study; dept.psy; dose time effect relation; nonhuman; pigeon; reinforcement; technique; variance

Varying initial-link and terminal-link durations in concurrent-chains schedules: a comparison of three models. - Mazur, James E (Behavioural Processes, 2004)
In Experiment 1, pigeons responded on concurrent-chains schedules with equal variable-interval schedules as initial links and fixed delays to food as terminal links. One terminal-link delay was always three times as long as the other. As terminal-link delays increased, response percentages on the key with the shorter terminal link increased according to a curvilinear function. This result supported the predictions of the hyperbolic value-added model and the contextual-choice theory but not delay-reduction theory. In Experiment 2, the terminal links were always delays of 2 s and 12 s, followed by food, and the durations of the initial links varied across conditions. As initial-link durations increased, pigeons' response percentages on the key with the shorter terminal link decreased, but toward an asymptote greater than 50%, indicating a continued preference for the shorter terminal link with very long initial links. This result was more consistent with the predictions of the hyperbolic-value added model than with those of the contextual-choice model or of delay-reduction theory. (C) 2004 Elsevier B.V. All rights reserved.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/023-773-022-282-811 tex.type: [object Object]
Keywords: *Behavior; Animal; *Reinforcement; Psychology; Animals; Behavior; Animal; Columba; Columbidae; Concurrent-chains schedule; Initial links; Key peck; Pigeons; Reinforcement (Psychology); Terminal links; Time Factors; animal experiment; behavioral response; bird; conference paper; controlled study; decision making; dept.psy; experiment; food; intermethod comparison; model; modeling; nonhuman; pigeon; prediction; reinforcement; response time; temporal analysis; theory

Two- versus three-alternative concurrent-chain schedules: a test of three models. - Mazur, James E (Journal of Experimental Psychology: Animal Behavior Processes, 2000)
Two experiments with pigeons used concurrent-chain procedures with variable-interval schedules as initial links and different delays to food as terminal links. Two schedules were present in all sessions. but a 3rd schedule was alternately present and absent in successive sessions. When the 3rd schedule delivered food with no terminal-link delay, the presence of this schedule led to an increase in preference for the schedule with the shorter terminal link of the 2 unchanged schedules. When the terminal-link delay for the 3rd schedule was 30 s, the presence of this schedule led to a decrease in preference for the schedule with the shorter terminal link of the 2 unchanged schedules. These results are inconsistent with the predictions of R. Grace's (1994) contextual-choice model, but they are consistent with 2 other mathematical models-delay-reduction theory and the hyperbolic value-added model.
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/030-282-629-182-734 tex.type: [object Object]
Keywords: *Choice Behavior; *Columbidae; *Conditioning; Operant; Analysis of Variance; Animals; Choice Behavior; Columbidae; Conditioning; Operant; Models; Psychological; analysis of variance; animal; article; decision making; dept.psy; instrumental conditioning; pigeons and doves; psychological model

Hyperbolic value addition and general models of animal choice - Mazur, James E. (Psychological Review, 2001)
Three mathematical models of choice-the contextual-choice model (R. Grace, 1994), delay-reduction theory (N. Squires & E. Fantino, 1971). and a new model called the hyperbolic value-added model-were compared in their ability to predict the results from a wide variety of experiments with animal subjects. When supplied with 2 or 3 free parameters, all 3 models made fairly accurate predictions for a large set of experiments that used concurrent-chain procedures. One advantage of the hyperbolic value-added model is that it is derived from a simpler model that makes accurate predictions for many experiments using discrete-trial adjusting-delay procedures. Some results favor the hyperbolic value-added model and delay-reduction theory over the contextual-choice model, but more data are needed from choice situations For which the models make distinctly different predictions.
Place: United States Mazur, J E. Department of Psychology, Southern Connecticut State University, New Haven, Connecticut 06515, USA. mazur@southernct.edu
Keywords: *Behavior; Animal; *Choice Behavior; *Models; Psychological; Animals; Behavior; Animal; Choice Behavior; Columbidae; Conditioning (Psychology); Conditioning; Psychological; Models; Psychological; Reinforcement (Psychology); Reinforcement Schedule; Reinforcement; Psychology; animal; animal behavior; comparative study; conditioning; decision making; dept.psy; pigeons and doves; psychological model; reinforcement; review; ⚠️ Invalid DOI

Evidence against a constant-difference effect in concurrent-chains schedules - Mazur, James E (Journal of the Experimental Analysis of Behavior, 2002)
Savastano and Fantino (1996) reported that in concurrent-chains schedules, initial-link choice proportions remained constant as terminal-link durations increased as long as the subtractive difference between the two terminal-link schedules remained constant. Two experiments with pigeons were conducted to examine this constant-difference effect. Both experiments used equal variable-interval schedules as initial links. The terminal links were fixed delays to reinforcement in Experiment 1 and variable delays to reinforcement in Experiment 2. The durations of the terminal links were varied across conditions, but the difference between pairs of terminal links was always 10 s. In both experiments, preference for the shorter terminal link became less extreme as terminal-link, durations increased, so a constant-difference effect was not found, It is argued, however, that this choice situation does not provide clear evidence for or against delay-reduction theory versus other theories of choice.
3 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Psychology Department, Southern Connecticut State University, New Heaven 06515, USA. mazur@southernct.edu
Keywords: *Choice Behavior; *Motivation; *Reinforcement Schedule; Animals; Appetitive Behavior; Choice Behavior; Color Perception; Columbidae; Concurrent-chains schedules; Delay-reduction theory; Fixed delays; Key peck; Mental Recall; Motivation; Pigeons; Reinforcement Schedule; Variable delays; animal; appetite; article; color vision; comparative study; decision making; dept.psy; motivation; peer-reviewed; pigeons and doves; recall; reinforcement

Exploring a concurrent-chains paradox: decreasing preference as an initial link is shortened. - Mazur, James E (Journal of experimental psychology. Animal behavior processes, 2005)
Experiments with pigeons and rats on concurrent-chains schedules examined a paradoxical effect reported by R. A. Preston and E. Fantino (1991). One schedule in the concurrent chain had a variable-interval (VI) 60-s initial link, and its terminal link was a 10-s delay to food. The other schedule had an initial link that ranged from VI 60 s to VI 2 s, and its terminal link was a 20-s delay to food. The paradoxical effect–a decrease in preference for the 20-s delay as its initial link was shortened–was found in some conditions but not in others. An analysis of response-reinforcer delays suggested that the paradoxical effect occurred in conditions in which responding on the short VI schedule almost always led to the 20-s delay, eliminating the possibility of switching to the alternative with the shorter delay. Copyright 2005 APA.
1 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Psychology Department, Southern Connecticut State University, New Haven, CT 06515, USA. mazurj1@southernct.edu
Keywords: *Choice Behavior; *Motivation; *Reinforcement Schedule; Animals; Association Learning; Choice Behavior; Color Perception; Columba; Columbidae; Discrimination Learning; Models; Psychological; Motivation; Psychomotor Performance; Reaction Time; Reinforcement Schedule; animal; article; color vision; decision making; dept.psy; discrimination learning; learning; motivation; pigeons and doves; psychological model; psychomotor performance; reaction time; reinforcement

Concurrent-chain performance in transition: effects of terminal-link duration and individual reinforcers. - Mazur, James E (Animal learning & behavior, 2002)
Pigeons responded on concurrent-chain schedules with variable-interval initial links and equal delays as terminal links. The terminal-link delays were 1 sec in some conditions and 20 sec in other conditions. The percentages of reinforcers delivered for responses on the left key were 10%, 30%, 70%, or 90%, and this percentage was switched every five to nine sessions. The rate of change in the pigeons' response percentages after a switch was the same whether the terminal-link delays were 1 sec or 20 sec. Analysis of the effects of individual reinforcers showed that after a response on one key had been reinforced, response percentages on that key were higher for at least the next 100 responses. Small effects of individual reinforcers were evident after eight or nine additional reinforcers had been delivered. The effects of individual reinforcers were about equally large during times of transition and during periods in which overall response percentages were relatively stable.
6 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Psychology Department, Southern Connecticut State University, New Haven, CT 06515, USA. mazur@southernct.edu
Keywords: *Behavior; Animal; *Reinforcement; Psychology; Animalia; Animals; Columba; Columbidae; Random Allocation; Reaction Time; Reinforcement Schedule; animal experiment; article; conditioned reflex; conditioning; decision making; dept.psy; nonhuman; pigeon; reinforcement; task performance

Effects of free-food deliveries and delays on choice under concurrent-chains schedules. - Mazur, James E (Behavioural Processes, 2003)
Pigeons responded on a concurrent-chains schedule with two equal variable-interval (VI) schedules as initial links and delays to food of 3 and 12 s as the two terminal links. In even-numbered sessions, no other reinforcement schedule was present, and all pigeons showed a strong preference for the response key that had the shorter, 3-s terminal-link delay. In odd-numbered sessions, the initial links were interrupted at random times by one of three different types of events. When the interruptions were immediate food deliveries, the response percentages increased on the key that had the 3-s delay. When the interruptions were 30-s delays followed by food, the response percentages remained approximately unchanged. When the interruptions were 30-s delays with no food, the response percentages decreased. The results were used to compare the predictions of different mathematical models of concurrent-chains performance. The results favored models that assume that preference is determined by the relative amount of advantage that is gained when a terminal link is entered. (C) 2003 Elsevier B.V. All rights reserved.
3 citations (Crossref) [2023-10-31] Place: Netherlands Mazur, James E.. Psychology Department, Southern Connecticut State University, 06515, New Haven, CT, USA
Keywords: Choice; Columba; Concurrent chains; Free food; Key peck; Pigeons; Reinforcer delay; animal behavior; animal experiment; article; controlled study; decision making; dept.psy; food; food deprivation; mathematical model; nonhuman; pigeon; prediction; preference behavior; reinforcement; stimulus response

Heuristics and general principles of learning. - Mazur, James E (Behavioural Processes, 2005)
This research on decision-making heuristics is similar to research on animal learning in at least two ways. First, optimality modeling has not proven to be very useful for either research area. Second, both of these research areas seek to find general principles (or heuristics) that are applicable to different species in different settings. However, the basic principles of classical and operant conditioning seem to be more uniform across species and situations, whereas decision-making heuristics can vary for different species and different situations, even for tasks with very similar characteristics.
0 citations (Crossref) [2023-10-31] Place: Netherlands Mazur, James E. Psychology Department, Southern Connecticut State University, New Haven, CT 06515, USA. mazurj1@southernct.edu
Keywords: *Algorithms; *Decision Making; *Learning; *Models; Psychological; Animalia; Animals; Decision-making; Heuristics; Humans; Optimality modeling; behavioral research; conditioned reflex; conference paper; decision making; dept.psy; heuristics; human; instrumental conditioning; learning; mental task; nonhuman

Learning and Behavior - Mazur, James E. (Pearson/Prentice Hall, 2006)
Keywords: Learning; Psychology of; Textbooks; Textbooks; Behavior modification; Textbooks; Conditioned response; Textbooks; Psychology; Comparative; dept.psy; faculty_collection

Learning and Behavior - Mazur, James E. (Pearson, 2013)
Keywords: Learning; Psychology of; Conditioned response; Behavior modification; Psychology; Comparative; dept.psy

Learning and Behavior. - Mazur, James E. (2004)
Keywords: dept.psy; faculty_collection; sabbatical_report

Choice behavior of pigeons (Columba livia), college students, and preschool children (Homo sapiens) in the Monty Hall dilemma. - Mazur, James E; Kahlbaugh, Patricia E (Journal of Comparative Psychology, 2012)
In the Monty Hall dilemma, an individual chooses between three options, only one of which will deliver a prize. After the initial choice, one of the nonchosen options is revealed as a losing option, and the individual can choose to stay with the original choice or switch to the other remaining option. Previous studies have found that most adults stay with their initial choice, although the chances of winning are 2/3 for switching and 1/3 for staying. Pigeons, college students, and preschool children were given many trials on this task to examine how their choices might change with experience. The college students began to switch on a majority of trials much sooner than the pigeons, contrary to the findings by Herbranson and Schroeder (2010) that pigeons perform better than people on this task. In all three groups, some individuals approximated the optimal strategy of switching on every trial, but most did not. Many of the preschoolers immediately showed a pattern of always switching or always staying and continued this pattern throughout the experiment. In a condition where the probability of winning was 90% after a switch, all college students and all but one pigeon learned to switch on nearly every trial. The results suggest that one main impediment to learning the optimal strategy in the Monty Hall task, even after repeated trials, is the difficulty in discriminating the different reinforcement probabilities for switching versus staying.
10 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Department of Psychology, Southern Connecticut State University, New Haven, CT 06515, USA. mazurj1@southernct.edu
Keywords: *Choice Behavior; *Columbidae; Adolescent; Animals; Child; Preschool; Choice Behavior; College students; Columbidae; Female; Games; Experimental; Humans; Male; Monty hall dilemma; Pigeons; Preschool children; Probability; Reinforcement Schedule; Reinforcement probability; Reward; Students; Students/px [Psychology]; Young Adult; adolescent; adult; animal; article; decision making; dept.psy; female; game; human; male; pigeons and doves; preschool child; probability; psychological aspect; reinforcement; reward; student

Tests of an indifference rule in variable-delay and double-reward choice procedures with humans - McKerchar, Todd L.; Mazur, James E. (Journal of the Experimental Analysis of Behavior, 2019)
Four hundred and fifty participants were recruited from Amazon Mechanical Turk across 3 experiments to test the predictions of a hyperbolic discounting equation in accounting for human choices involving variable delays or multiple rewards (Mazur, 1984, 1986). In Experiment 1, participants made hypothetical choices between 2 monetary alternatives, 1 consisting of a fixed delay and another consisting of 2 delays of equal probability (i.e., a variable-delay procedure). In Experiment 2, participants made hypothetical monetary choices between a single, immediate reward and 2 rewards, 1 immediate and 1 delayed (i.e., a double-reward procedure). Experiment 3 also used a double-reward procedure, but with 2 delayed rewards. Participants in all 3 experiments also completed a standard delay-discounting task. Finally, 3 reward amounts were tested in each type of task ($100, $1000, and $5000). In the double-reward conditions (Experiments 2 and 3), the results were in good qualitative and quantitative agreement with Mazur's model (1984, 1986). In contrast, when participants made choices involving variable delays (Experiment 1), there was relatively poor qualitative and quantitative agreement with this model. These results, along with our previous findings, suggest the structure of questions in hypothetical tasks with humans can be a strong determinant of the choice pattern.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/054-652-829-640-61X tex.address: [object Object] tex.affiliation: [object Object] tex.author-email: [object Object] tex.da: [object Object] tex.doc-delivery-number: [object Object] tex.eissn: [object Object] tex.journal-iso: [object Object] tex.keywords-plus: [object Object] tex.number-of-cited-references: [object Object] tex.publisher: [object Object] tex.research-areas: [object Object] tex.researcherid-numbers: [object Object] tex.times-cited: [object Object] tex.type: [object Object] tex.unique-id: [object Object] tex.usage-count-last-180-days: [object Object] tex.usage-count-since-2013: [object Object] tex.web-of-science-categories: [object Object]
Keywords: Adult; Choice Behavior; Delay Discounting; Female; Humans; Male; Models; Psychological; Probability; Reward; adult; choice; decision making; delay discounting; dept.psy; female; human; humans; hyperbolic discounting; male; mathematical model; peer-reviewed; probability; psychological model; reward

Pigeons' choices with token stimuli in concurrent variable-interval schedules: concurrent vi schedules with tokens - Mazur, James E; Biondi, Dawn R (Journal of the Experimental Analysis of Behavior, 2013)
Twelve pigeons responded on concurrent variable-interval schedules that delivered token stimuli (stimulus lights for some pigeons, and white circles on the response keys for others). During exchange periods, each token could be exchanged for food on a fixed-ratio 1 schedule. Across conditions, the exchange requirements ( number of tokens that had to be earned before they could be exchanged for food) varied between one and four for the two response keys. The main findings were that the pigeons' response percentages varied as a function of the number of tokens earned at any given moment, and they were determined by both the delays to food and by the number of food deliveries in the exchange periods. In some conditions, tokens had to be earned but were not visible during the variable-interval schedules for one or both keys. When one key had visible tokens and the other did not, the pigeons showed a preference for the key without visible tokens. A model based on the matching law and a hyperbolic delay-discounting equation could account for the main patterns of choice responding, and for how response percentages changed as successive tokens were earned. The results are consistent with the view that the token stimuli served as discriminative stimuli that signaled the current delays to food.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/055-953-404-245-599, lens.org/132-483-465-914-642 tex.type: [object Object]
Keywords: *Choice Behavior; *Token Economy; Animals; Columbidae; Concurrent variable-interval schedules; Conditioning; Operant; Generalized matching law; Hyperbolic discounting; Keypeck; Male; Models; Psychological; Pigeons; Reinforcement Schedule; Token stimuli; dept.psy; peer-reviewed

Human choices between variable and fixed rewards in hypothetical variable‐delay and double‐reward discounting procedures - McKerchar, Todd L.; Mazur, James E. (Journal of the Experimental Analysis of Behavior, 2016)
Prior research has shown that nonhumans show an extreme preference for variable-over fixed-delays to reinforcement. This well-established preference for variability occurs because a reinforcer's strength or “value” decreases according to a curvilinear function as its delay increases. The purpose of the present experiments was to investigate whether this preference for variability occurs with human participants making hypothetical choices. In three experiments, participants recruited from Amazon Mechanical Turk made choices between variable and fixed monetary rewards. In a variable-delay procedure, participants repeatedly chose between a reward delivered either immediately or after a delay (with equal probability) and a reward after a fixed delay (Experiments 1 and 2). In a double-reward procedure, participants made choices between an alternative consisting of two rewards, one delivered immediately and one after a delay, and a second alternative consisting of a single reward delivered after a delay (Experiments 1 and 3). Finally, all participants completed a standard delay-discounting task. Although we observed both curvilinear discounting and magnitude effects in the standard discounting task, we found no consistent evidence of a preference for variability-as predicted by two prominent models of curvilinear discounting (i.e., a simple hyperbola and a hyperboloid)-in our variable-delay and double-reward procedures. This failure to observe a preference for variability may be attributed to the hypothetical, rule-governed nature of choices in the present study. In such contexts, participants may adopt relatively simple strategies for making more complex choices.
3 citations (Crossref) [2023-10-31] Citation Key Alias: pop00258 tex.type: [object Object]
Keywords: dept.psy; peer-reviewed

Effects of time between trials on rats' and pigeons' choices with probabilistic delayed reinforcers. - Mazur, James E; Biondi, Dawn R (Journal of the Experimental Analysis of Behavior, 2011)
Parallel experiments with rats and pigeons examined reasons for previous findings that in choices with probabilistic delayed reinforcers, rats' choices were affected by the time between trials whereas pigeons' choices were not. In both experiments, the animals chose between a standard alternative and an adjusting alternative. A choice of the standard alternative led to a short delay (1 s or 3 s), and then food might or might not be delivered. If food was not delivered, there was an "interlink interval," and then the animal was forced to continue to select the standard alternative until food was delivered. A choice of the adjusting alternative always led to food after a delay that was systematically increased and decreased over trials to estimate an indifference point–a delay at which the two alternatives were chosen about equally often. Under these conditions, the indifference points for both rats and pigeons increased as the interlink interval increased from 0 s to 20 s, indicating decreased preference for the probabilistic reinforcer with longer time between trials. The indifference points from both rats and pigeons were well described by the hyperbolic-decay model. In the last phase of each experiment, the animals were not forced to continue selecting the standard alternative if food was not delivered. Under these conditions, rats' choices were affected by the time between trials whereas pigeons' choices were not, replicating results of previous studies. The differences between the behavior of rats and pigeons appears to be the result of procedural details, not a fundamental difference in how these two species make choices with probabilistic delayed reinforcers.
15 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Psychology Department, Southern Connecticut State University, New Haven, CT 06515, USA. mazurj1@southernct.edu
Keywords: *Choice Behavior; *Memory; Short-Term; *Probability Learning; *Reinforcement Schedule; Animals; Choice Behavior; Columbidae; Conditioning; Operant; Long Evans rat; Male; Memory; Short-Term; Motivation; Probability Learning; Psychomotor Performance; Rats; Rats; Long-Evans; Reinforcement Schedule; Species Specificity; Time Perception; animal; article; decision making; dept.psy; instrumental conditioning; learning; male; motivation; peer-reviewed; pigeons and doves; psychomotor performance; rat; reinforcement; short term memory; species difference; time perception

Delay-amount tradeoffs in choices by pigeons and rats: hyperbolic versus exponential discounting. - Mazur, James E; Biondi, Dawn R (Journal of the Experimental Analysis of Behavior, 2009)
An adjusting-delay procedure was used to study the choices of pigeons and rats when both delay and amount of reinforcement were varied. In different conditions, the choice alternatives included one versus two reinforcers, one versus three reinforcers, and three versus two reinforcers. The delay to one alternative (the standard alternative) was kept constant in a condition, and the delay to the other (the adjusting alternative) was increased or decreased many times a session so as to estimate an indifference point–a delay at which the two alternatives were chosen about equally often. Indifference functions were constructed by plotting the adjusting delay as a function of the standard delay for each pair of reinforcer amounts. The experiments were designed to test the prediction of a hyperbolic decay equation that the slopes of the indifference functions should increase as the ratio of the two reinforcer amounts increased. Consistent with the hyperbolic equation, the slopes of the indifference functions depended on the ratios of the two reinforcer amounts for both pigeons and rats. These results were not compatible with an exponential decay equation, which predicts slopes of 1 regardless of the reinforcer amounts. Combined with other data, these findings provide further evidence that delay discounting is well described by a hyperbolic equation for both species, but not by an exponential equation. Quantitative differences in the y-intercepts of the indifference functions from the two species suggested that the rate at which reinforcer strength decreases with increasing delay may be four or five times slower for rats than for pigeons.
71 citations (Crossref) [2023-10-31] Place: United States Mazur, James E. Department, Southern Connecticut State University, New Haven, CT 06515, USA. mazurj1@southernct.edu
Keywords: *Choice Behavior; *Reinforcement Schedule; Animals; Choice Behavior; Columbidae; Conditioning; Operant; Long Evans rat; Male; Models; Psychological; Rats; Rats; Long-Evans; Reinforcement Schedule; Reward; animal; article; decision making; dept.psy; instrumental conditioning; male; peer-reviewed; pigeons and doves; psychological model; rat; reinforcement; reward

Transitional choice behavior in concurrent-chain schedules - Mazur, James E; Blake, Nancy; Mcmanus, Courtney (Behavioural Processes, 2001)
The choice responses of four pigeons were examined in 20 periods of transition in a concurrent-chain procedure with variable-interval schedules as initial links and fixed delays to reinforcement as terminal links. In some conditions, the delays to reinforcement were different for the two terminal links, and changes in preference were recorded after the delays for the two response keys were switched. In other conditions, the reinforcer delays were equal for the two keys, but which key delivered 80% of the reinforcers was periodically switched. Choice proportions changed more quickly after a switch in reinforcement percentages chan after a switch in the delays, thereby contradicting the hypothesis that faster changes would occur when the switch in conditions was easier to discriminate. Analyses of response sequences showed that the effects: of individual reinforcers were larger and lasted longer in conditions with changing reinforcement percentages than in conditions with changing terminal-link delays. Rates of change in choice behavior do not appear to be limited by the unpredictability of variable reinforcement schedules, because the changes in behavior were slow and gradual even when there was a large and sudden change in reinforcer delays. (C) 2001 Elsevier Science B.V. All rights: reserved.
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-721-068-778-123 tex.type: [object Object]
Keywords: Columba; Concurrent-chain schedules; Transitional choice behavior; animal experiment; article; behavior; controlled study; decision making; dept.psy; instrumental conditioning; nonhuman; pigeon; reinforcement; stimulus response